Current Models to Study the Sporothrix-Host Interaction - Vargas-Macías, Ana P.; Gómez-Gaviria, Manuela; García-Carnero, Laura C.; Mora-Montes, Héctor M. (Frontiers in Fungal Biology, 2022)
Sporotrichosis is a worldwide distributed subcutaneous mycosis that affects mammals, including human beings. The infection is caused by members of the Sporothrix pathogenic clade, which includes Sporothrix schenckii, Sporothrix brasiliensis, and Sporothrix globosa. The fungus can be acquired through traumatic inoculation of conidia growing in vegetal debris or by zoonotic transmission from sick animals. Although is not considered a life-threatening disease, it is an emergent health problem that affects mostly immunocompromised patients. The sporotrichosis causative agents differ in their virulence, host range, and sensitivity to antifungal drugs; therefore, it is relevant to understand the molecular bases of their pathogenesis, interaction with immune effectors, and mechanisms to acquired resistance to antifungal compounds. Murine models are considered the gold standard to address these questions; however, some alternative hosts offer numerous advantages over mammalian models, such as invertebrates like Galleria mellonella and Tenebrio molitor, or ex vivo models, which are useful tools to approach questions beyond virulence, without the ethical or budgetary features associated with the use of animal models. In this review, we analyze the different models currently used to study the host-Sporothrix interaction.